ANALISIS POTENSI ENERGI LISTRIK DI GEDUNG UMPAR MENGGUNAKAN PANEL SURYA 100WP - Alauddin Y; Ashadi Amir; Asrul Asrul; Sudirman Sahidin (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2023)
Electricity plays a very important role in everyday life. Most human activities are related to the use of electrical energy, including in the Campus environment. Technological advances have resulted in an increase in the consumption of electrical energy and this has resulted in reduced reserves of fossil energy sources as a result of being used up and causing emissions that can affect the global climate. The energy transition from the use of fossil energy to new and renewable energy is one solution to overcome this. Solar Power Plant (PLTS) is an alternative energy solution that is environmentally friendly that can be developed on campus. This is also supported by Indonesia's geographical location which has a very high intensity of sunlight. In this study, an analysis of the potential of electrical energy generated at Universitas Muhammadiyah Parepare Building was carried out. The research was conducted by measuring the surface voltage and temperature of solar panels for 20 days. The test was carried out for 7 hours from 10.00 WITA to 16.00 WITA. Voltage and temperature measurements were carried out in 1 hour intervals. The test results show that the average voltage value generated by solar panels is 21.31 volts. The highest average voltage value was generated at 13.00 WITA, which was 21.82 volts with an average surface temperature of 37.79 oC